2007
DOI: 10.1111/j.1099-1123.2007.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal Audit Departments: Adoption and Characteristics in Italian Companies

Abstract: This article analyses the adoption and characteristics of internal audit departments in Italian companies, in the light of recent changes in the economic and political environment following the big financial scandals which occurred both in Italy and abroad. The research framework is informed by new institutional theory, driving the definition of a conceptual model. The research approach comprises two steps: first, a preliminary in-depth case study to support the research design (assessment of relevant variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 38 publications
(57 reference statements)
4
68
1
4
Order By: Relevance
“…Institutional theory could, therefore, enable a study of internal audit from diverse perspectives compared to the limited and limiting principal-agent (shareholder-manager) focus of agency theory. Moreover, prior research suggests the validity of this theory for internal audit research in the contexts of both developing (see example, Al-Twaijry et al, 2003) and developed economies (see example, Arena et al, 2006;Arena and Azzone, 2007).…”
Section: Institutional Theorymentioning
confidence: 96%
“…Institutional theory could, therefore, enable a study of internal audit from diverse perspectives compared to the limited and limiting principal-agent (shareholder-manager) focus of agency theory. Moreover, prior research suggests the validity of this theory for internal audit research in the contexts of both developing (see example, Al-Twaijry et al, 2003) and developed economies (see example, Arena et al, 2006;Arena and Azzone, 2007).…”
Section: Institutional Theorymentioning
confidence: 96%
“…Several previous studies on internal audit have drawn on the institutional theory (Al-Twaijry et al, 2003;Arena & Azzone, 2006;Arena & Azzone, 2007;Mihret et al, 2010). Empirical works cited from these studies tend to suggest that the institutional theory is a valid theory for internal audit effectiveness which has been employed in both developed and developing regions.…”
Section: Theories Of Internal Auditingmentioning
confidence: 99%
“…85.37 percent of the private sector IAF being involved in out sourcing compared to 67 percent of public sector internal audit being involved in outsourcing. Previous studies of [21] indicated that 69.41 percent of Italian firms do not outsourced internal audit services. Whereas, [13] indicated that 68 percent of public sector entities and 65 percent private sector entities engaged in outsourcing internal audit services.…”
Section: Resultsmentioning
confidence: 98%